Hubungan antara indeks massa tubuh, aktivitas fisik, kualitas tidur, dan kebugaran fisik pada remaja - Kurniawan, Irfan; Yuliarto, Hari; Sujarwo, Sujarwo (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2023)
This study aims to determine the relationship between BMI, physical activity, and sleep quality with physical fitness and the correlation between these factors. The research method used is correlational research. The subjects of this study were adolescent students aged 16-19 years. It selected subjects using purposive sampling techniques with criteria of adolescents aged 16-19, healthy conditions, and willingness to participate in research activities. The total subjects involved were 251 teenagers. The research instruments used were BMI measurement, physical activity using the PAQ-A questionnaire, sleep quality measured using PSQI, and physical fitness measured using the Indonesian Physical Fitness Test for the age range of 16-19 years. The data analysis techniques used are descriptive analysis and multiple regression tests. The results showed that BMI and physical fitness were significantly associated with an effective contribution of 4.29%, physical activity, and physical fitness had a significant relationship with an effective contribution of 46.34%, and sleep quality and physical fitness were significantly associated with an effective contribution of 2.27%. The BMI, physical activity, and sleep quality all had a significant relationship with physical fitness in adolescent students, with an effective contribution of 53.40%, meaning that it was concluded that there was a relationship between BMI, physical activity, sleep quality, and physical fitness. The results of this study answered that BMI, physical activity, and sleep quality contribute to the fitness of adolescent students.